2017
DOI: 10.2174/1567205013666160620115130
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/MR Imaging in Major Neurocognitive Disorders

Abstract: PET/MRI tomographs represent the latest development in hybrid molecular imaging, opening new perspectives for clinical and research applications and attracting a large interest among the medical community. This new hybrid modality is expected to play a pivotal role in a number of clinical applications and among these the assessment of neurodegenerative disorders. PET and MRI, acquired separately, are already the imaging biomarkers of choice for a comprehensive assessment of the changes occurring in dementias (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 114 publications
(141 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the use of hybrid PET/MR acquisition and and in the hemibody contralateral to the treatment (ΔUPDRS-treated). c Whole-brain voxel-wise correlation analysis confirmed significant correlation in the STN and finds a significantly positive correlation in the mid putamen PVE correction in the current study may contribute to increase the sensitivity in discriminating between metabolic brain states [30,31].…”
Section: Effect On Motor Cortical Regionssupporting
confidence: 70%
“…Furthermore, the use of hybrid PET/MR acquisition and and in the hemibody contralateral to the treatment (ΔUPDRS-treated). c Whole-brain voxel-wise correlation analysis confirmed significant correlation in the STN and finds a significantly positive correlation in the mid putamen PVE correction in the current study may contribute to increase the sensitivity in discriminating between metabolic brain states [30,31].…”
Section: Effect On Motor Cortical Regionssupporting
confidence: 70%
“…Cerebral amyloid angiopathy diagnosis might be improved by combining the complementary information of lobar CMBs and β amyloid burden. The newly emerging PET/MR imaging method integrates the advantages of PET and MR and has been used to diagnose and monitor patients with various neurodegenerative conditions (Mainta et al, 2017). To our knowledge, no study has investigated the diagnostic value of combining amyloid deposition and CMB distribution, specifically in CAA and AD patients and cognitively normal healthy controls (NC) using integrated PET/MR.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated positron emission tomography (PET) / magnetic resonance (MR) systems have been currently widely distributed (over 100 institutions in the world). Previous studies have revealed that 2-deoxy-2-[18F]fluoro-D-glucose (FDG)-PET/MR is useful in the evaluation of neurodegenerative diseases [1][2][3][4][5][6]. Additionally, combined PET/MR not only provides detailed brain anatomy, but the immediate availability of coregistered anatomy might even improve PET image quality by facilitating the correction of partial volume effects and/or motion artifacts [7,8].…”
Section: Introductionmentioning
confidence: 99%